Lithium-ion batteries, batteries and power-consuming devices
Patent Information
- Application Number
- JP2024543966
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-30
- Filing Date
- 2024-02-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-02-05
AI Technical Summary
【0087】 推定される有益な効果は、以下のとおりである。環状カーボネートの質量含有量とヘキサフルオロリン酸リチウムの質量含有量との比が上記範囲にある場合、ヘキサフルオロリン酸リチウムからより多くのリチウムイオンを十分に解離させることに有利であり、それにより低SOCの放電末期においても、電解液系により多くのリチウムイオンを含有させることができ、且つリチウムイオンを電池反応の進行に伴って連続的に解離させることができ、電池のパワー性能を改善する。
Smart Images

Figure 2025505532000001_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to Chinese Patent Application No. 202311422403.0, entitled "Lithium-ion Battery, Battery and Power Consumption Device," filed on October 30, 2023, the entire contents of which are incorporated herein by reference. [Technical field]
[0002] This application relates to lithium ion batteries, batteries and power consuming devices. [Background technology]
[0003] Lithium ion batteries have characteristics such as high capacity and long life, and are therefore widely used in electronic devices, such as mobile phones, notebook computers, battery cars, electric cars, electric airplanes, electric steamships, electric toy cars, electric toy steamships, electric toy airplanes and electric tools, etc. Lithium ion batteries have made great progress, and therefore higher requirements are being placed on the performance of lithium ion batteries.
[0004] However, the cycle performance of current lithium-ion batteries is still low. Summary of the Invention
[0005] The present application provides a lithium-ion battery, a battery and a power consuming device, and the cycling performance of the lithium-ion battery described in the present application is relatively low.
[0006] According to a first aspect, an embodiment of the present application provides a lithium ion battery, the lithium ion battery comprising an electrolyte and a positive electrode plate, the electrolyte comprising a lithium salt, the lithium salt comprising lithium hexafluorophosphate, the mass content of the lithium hexafluorophosphate being 15% to 20% relative to the total mass of the electrolyte, the positive electrode plate comprising a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector and containing a positive electrode active material, the positive electrode active material having a molecular formula of Li d Ni a Co bMn c M (1-a-b-c) Q z and contains a compound where 0 < d ≤ 2.1, 0.6 < a < 1, 0 < b < 1, 0 < c < 1, and 0.6 < a + b + c < 1, 1.8 ≤ z ≤ 3.5. The M element contains at least one element among B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, Ce. The Q element contains at least one element among O, F.
[0007] Thus, the nickel element content in the cathode active material in the embodiments of the present application is relatively high. To improve the stability of the cathode active material structure, the cathode active material in the embodiments of the present application further contains the M element. The introduction of the M element can improve the stability of the cathode active material crystal structure and the cycle performance of the lithium-ion battery. However, as the cycle progresses, both the metal elements and non-metal elements in the cathode active material have a risk of elution. The eluted metal elements and non-metal elements can move to the surface of the negative electrode plate through the electrolyte, destroy the solid electrolyte interphase (SEI) film on the surface of the negative electrode plate, and may precipitate as a metal single body on the surface of the negative electrode plate, thereby deteriorating the cycle performance. The embodiments of the present application further combine a high content of lithium hexafluorophosphate. The mass content of lithium hexafluorophosphate LiPF6 in the total mass of the electrolyte is 15% to 20%. The high content of lithium hexafluorophosphate can form a protective layer with lithium fluoride LiF as the main film component on the surface of the cathode active material, thereby alleviating the elution of metal elements and non-metal elements to a certain extent and further improving the cycle performance of the lithium-ion battery.
[0008] In some embodiments, the M element contains at least one element among Ti and Zr, the electrolyte contains a first additive, and the first additive contains at least one of lithium difluoro(oxalato)borate LiDFOB and lithium tetrafluoroborate LiBF4.
[0009] As a result, in the later cycle of the lithium ion battery, there is a risk that metal ions, such as Ti and Zr ions, in the positive electrode active material will dissolve into the electrolyte and migrate to the surface of the negative electrode plate; the first additive contains fluorine ions and boron ions, which have a relatively strong bonding ability with the above metal ions, and can reduce the risk of the metal ions migrating to the surface of the negative electrode plate, thereby improving the cycle performance of the lithium ion battery; and although the Ti and Zr ions can improve the structural stability of the material, they may adversely affect the conduction of lithium ions in the crystal lattice, causing power degradation; the first additive can further compensate for the power degradation caused by the Ti and Zr ions.
[0010] In some embodiments, the M element includes Ti and Zr elements. When M includes Ti and Zr elements at the same time, the two elements can be used together to further stabilize the material structure and improve the cycle performance.
[0011] In some embodiments, the mass content of the Ti element is 100 ppm to 600 ppm, based on the total mass of the positive electrode active material, and / or the mass content of the Zr element is 500 ppm to 2550 ppm, based on the total mass of the positive electrode active material, and the mass content of the first additive is 30 ppm to 1200 ppm, optionally 100 ppm to 400 ppm, based on the total mass of the electrolyte.
[0012] In some embodiments, the cathode active material comprises a single crystal particle, the single crystal particle comprises an inner region and an outer region, the outer region is a region extending 500 nm from any point on the outer surface of the single crystal particle directly toward the inside of the single crystal particle, and the M element comprises an Al element, the Al element being distributed in at least the outer region. The aluminum Al element being distributed in at least the outer region serves to form aluminum oxide Al2O3 in the cathode active material, which can passivate the side reaction between the cathode active material and the electrolyte, further improve the stability of the cathode active material structure, and improve the cycle performance of the lithium ion battery.
[0013] In some embodiments, the electrolyte comprises a second additive, and the second additive comprises lithium difluorophosphate. The lithium difluorophosphate LiPO2F2 can be combined with the Al element in the positive electrode active material to improve the DCR of the surface of the positive electrode active material and enhance the interfacial power.
[0014] In some embodiments, based on the total mass of the positive electrode active material, the mass content of the Al element is 500 ppm to 3000 ppm, and based on the total mass of the electrolyte, the mass content of the second additive is 100 ppm to 3000 ppm.
[0015] In some embodiments, the M element further comprises at least one of P, S and B, where at least one of P, S and B is distributed in the outer region, and the electrolyte comprises a third additive, where the third additive comprises lithium fluorosulfonate. The phosphorus P, sulfur S and boron B elements are absorbed in the oxygen layer and act to stabilize lithium, thereby improving the stability of the positive electrode active material structure and improving the cycle performance of the lithium ion battery.
[0016] In some embodiments, based on the total mass of the positive electrode active material, the total mass content of the P, S and B elements is 10 ppm to 800 ppm, based on the total mass of the electrolyte, the mass content of the third additive is 50 ppm to 200 ppm. The third additive can be combined with the phosphorus P, sulfur S and boron B elements in the positive electrode active material to reduce the DCR of the surface of the positive electrode active material and improve the interfacial power.
[0017] In some embodiments, the electrolyte contains a cyclic carbonate, and the ratio of the mass content of the cyclic carbonate to the mass content of lithium hexafluorophosphate, based on the total mass of the electrolyte, is (0.60 to 2.50): 1, and optionally (1.00 to 1.65): 1. When the ratio of the mass content of the cyclic carbonate to the mass content of lithium hexafluorophosphate is within the above range, it is advantageous to sufficiently dissociate more lithium ions from lithium hexafluorophosphate, so that even at the end of discharge with a low SOC, more lithium ions can be contained in the electrolyte system, and lithium ions can be continuously dissociated as the battery reaction proceeds, improving the power performance of the battery.
[0018] In some embodiments, the mass content of the cyclic carbonate is 20% to 30% based on the total mass of the electrolyte solution, and / or the cyclic carbonate includes at least one of ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). Cyclic carbonates have high dielectric constants and high ionic conductivity, and can form a stable SEI film on the surface of the negative electrode active material.
[0019] In some embodiments, the lithium ion battery further includes a negative electrode plate, the negative electrode plate including a negative electrode current collector and a negative electrode film layer provided on at least one side of the negative electrode current collector and including a negative electrode active material, the negative electrode active material including a carbon element and a silicon element, and a ratio of the mass content of the silicon element to the mass content of the carbon element based on the total mass of the negative electrode active material is from (0.3:99.7) to (3:97).
[0020] As a result, the negative electrode active material simultaneously includes a carbon-based material and a silicon-based material, and the lithium release voltage plateau of the silicon-based material is relatively high compared to the carbon-based material, so that the silicon-based material can still continue to participate in the discharge even under low SOC (e.g., SOC≦10%), which makes up for the shortcoming of the carbon-based material that is difficult to discharge / cannot continue to discharge at low SOC, improves the direct current internal resistance DCR during the discharge process of the battery, and further improves the power performance during the discharge process of the battery. The electrolyte of the embodiment of the present application further uses 15% to 20% lithium hexafluorophosphate in combination, and improves the power performance of the battery at the end of discharge through the cooperation between the electrolyte and the negative electrode.
[0021] In some embodiments, the electrolyte comprises a fluorinated cyclic carbonate, and the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of elemental silicon relative to the total mass of the electrolyte is (0.5 to 9.5):1, optionally (1 to 2):1.
[0022] Thus, the fluorinated cyclic carbonate can participate in the formation of an SEI film on the surface of the negative electrode active material, improve the film components and properties, and effectively protect the negative electrode active material. In particular, when the negative electrode contains silicon, due to the property of silicon expanding, the film composition of the SEI film formation needs to be further optimized. The optimization of the film composition can be adjusted by adjusting the relative ratio of the film-forming additive in the electrolyte. The fluorinated cyclic carbonate can participate in the film formed to improve the flexibility of the SEI film, and can improve the structural collapse caused by silicon releasing a large amount of lithium ions in a short period of time at the end of discharge. In addition, the fluorinated cyclic carbonate has a certain desolvation ability, which is favorable for the migration of lithium ions, and can improve the DCR at low SOC and improve the discharge power.
[0023] In some embodiments, the mass content of the fluorinated cyclic carbonate is from 0.95% to 5.8%, optionally from 1.5% to 3%, based on the total mass of the electrolyte, and / or the fluorinated cyclic carbonate comprises at least one of monofluoroethylene carbonate FEC, bisfluoroethylene carbonate DFEC, trifluoropropylene carbonate TFPC, optionally the fluorinated cyclic carbonate comprises monofluoroethylene carbonate FEC.
[0024] In some embodiments, the ratio of the packed density of the positive electrode membrane layer to the packed density of the negative electrode membrane layer is (2 to 2.5): 1. Optionally, the packed density of the positive electrode membrane layer is 3.0 g / cm 3 to 3.5 g / cm 3 and the compaction density of the negative electrode film layer is 1.3 g / cm 3 to 1.7 g / cm 3 It is.
[0025] In some embodiments, the electrolyte further comprises a fourth additive, the fourth additive comprising at least one of 1,3-propane sultone PS, vinylene carbonate VC, and lithium fluorosulfonate LiSO3F. The above components can essentially participate in the formation of an SEI film on the surface of the negative electrode active material, and the SEI film can effectively mitigate the expansion of the silicon-based material.
[0026] In some embodiments, the mass content of 1,3-propane sultone PS is 0.1% to 1%, based on the total mass of the electrolyte, and / or the mass content of vinylene carbonate VC is 0.1% to 1%, based on the total mass of the electrolyte, and / or the mass content of lithium fluorosulfonate LiSO3F is 0.1% to 1%, based on the total mass of the electrolyte.
[0027] According to a second aspect, the present application further provides a battery comprising the lithium ion battery according to any embodiment of the first aspect of the present application.
[0028] According to a third aspect, the present application further provides a power consuming device, the power consuming device comprising a battery according to any one of the embodiments of the second aspect of the present application. [Brief description of the drawings]
[0029] In order to more clearly explain the technical solutions of the embodiments of the present application, the following briefly introduces drawings that need to be used in the embodiments of the present application. It is obvious that the drawings in the following description are only some embodiments of the present application, and those skilled in the art can also obtain other drawings based on the drawings without exerting creative efforts. [Figure 1] FIG. 1 is a schematic diagram of one embodiment of a lithium-ion battery of the present application. [Diagram 2] FIG. 2 is an exploded schematic view of an embodiment of the lithium-ion battery of FIG. [Diagram 3] FIG. 1 is a schematic diagram of one embodiment of a battery module of the present application. [Figure 4] FIG. 1 is a schematic diagram of one embodiment of a battery pack of the present application. [Diagram 5] 5 is an exploded schematic view of the embodiment of the battery pack shown in FIG. 4. [Figure 6] 1 is a schematic diagram of one embodiment of the present application including a lithium-ion battery-powered power consumer device.The drawings are not necessarily drawn to scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing the lithium ion battery, battery, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and repeated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily redundant and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0031] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60 to 120 and 80 to 110 are listed for a particular parameter, it is understood that ranges of 60 to 110 and 80 to 120 are also envisioned. However, if 1 and 2 are listed as minimum range values, and 3, 4, and 5 are listed as maximum range values, then ranges such as 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4, and 2 to 5 are all envisioned. In this application, unless otherwise specified, a numerical range "a to b" represents a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0 to 5" represents a listing of all real numbers between "0 and 5" herein, and "0 to 5" is merely a shorthand representation of combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0032] Unless otherwise stated, all the embodiments and optional embodiments in the present application can be combined with each other to form a new technical solution.
[0033] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0034] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, and preferably in sequence. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method mentioned above may further include step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.
[0035] Charge-discharge batteries generally include ion batteries and metal batteries, and metal batteries, such as lithium metal batteries and sodium metal batteries, have relatively high negative electrode activity and a relatively high risk of generating dendrites, resulting in relatively low battery reliability. Ion batteries have relatively high reliability and are therefore widely used.
[0036] A lithium ion battery generally includes an electrode assembly and an electrolyte, the electrode assembly including a positive electrode plate, a negative electrode plate, and a separator, the separator being disposed between the positive electrode plate and the negative electrode plate to separate the positive electrode plate and the negative electrode plate, the positive electrode plate including a positive electrode membrane layer containing a positive electrode active material, the positive electrode active material being a donor through which the lithium ion battery provides lithium ions, the negative electrode plate including a negative electrode membrane layer containing a negative electrode active material, the negative electrode active material being a receptor for lithium ions, and the electrolyte providing a migration path for lithium ions between the positive electrode plate and the negative electrode plate.
[0037] In order to improve the energy density of a lithium-ion battery, a positive electrode active material with a relatively high capacity is generally used, for example, the nickel content in the positive electrode active material is increased. However, as the nickel content increases, the structure of the positive electrode active material is prone to generate microcracks during cycling, which causes the structure of the positive electrode active material to be destroyed and even collapse. Especially in the later stage of cycling, the cumulative destruction degree of the positive electrode active material increases, resulting in poor cycle performance.
[0038] In view of the above problems, an embodiment of the present application provides a lithium ion battery, the positive electrode active material of the lithium ion battery having a molecular formula of Li d Ni a Co b Mn c M (1-a-b-c) Y zA compound is included, where 0 < d ≤ 2.1, 0.6 < a < 1, 0 < b < 1, 0 < c < 1, and 0.6 < a + b + c ≤ 1, 1.8 ≤ z ≤ 3.5. The M element contains at least one element among B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, Ce. The Y element contains at least one element among O, F. The nickel element content of this cathode active material is relatively high. To improve the stability of the cathode active material structure, the cathode active material of the embodiment of this application further contains the M element. The introduction of the M element can improve the stability of the cathode active material crystal structure and the cycle performance of the lithium-ion battery. However, as the cycle progresses, both the metal elements and non-metal elements in the cathode active material have a risk of elution. The eluted metal elements and non-metal elements can move to the surface of the negative electrode plate through the electrolyte and deteriorate the cycle life. The embodiment of this application further combines a high content of lithium hexafluorophosphate. The mass content of lithium hexafluorophosphate LiPF6 in the total mass of the electrolyte is 15% to 20%. The high content of lithium hexafluorophosphate can form a protective layer with lithium fluoride LiF as the main film component on the surface of the cathode active material, thereby alleviating the elution of metal elements and non-metal elements to a certain extent and further improving the cycle performance of the lithium-ion battery. Next, the technical solution of this application will be described in detail.
[0039] Lithium-ion battery According to a first aspect, an embodiment of this application provides a lithium-ion battery. The lithium-ion battery includes an electrolyte and a cathode plate. The electrolyte contains a lithium salt. The lithium salt contains lithium hexafluorophosphate. The mass content of lithium hexafluorophosphate in the total mass of the electrolyte is 15% to 20%. The cathode plate contains a cathode current collector and a cathode film layer provided on at least one side of the cathode current collector and containing a cathode active material. The cathode active material has a molecular formula of Li d Ni a Co b Mn c M(1-a-b-c) Q z and contains a compound where 0 < d ≤ 2.1, 0.6 < a < 1, 0 < b < 1, 0 < c < 1, and 0.6 < a + b + c < 1, 1.8 ≤ z ≤ 3.5, the M element contains at least one element among B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, Ce, and the Q element contains at least one element among O, F.
[0040] Since the nickel element content of the positive electrode active material is relatively high, in order to improve the stability of the positive electrode active material structure or improve other characteristics advantageous to the electrical performance of the positive electrode active material, the positive electrode active material of the embodiments of the present application further contains an M element. The introduction of the M element can improve the stability of the positive electrode active material crystal structure and improve the cycle performance of the lithium-ion battery. However, as the cycle progresses, both the metal elements and non-metal elements in the positive electrode active material have a risk of elution. The eluted metal elements and non-metal elements can move to the surface of the negative electrode plate through the electrolyte, destroy the solid electrolyte interphase (SEI) film on the surface of the negative electrode plate, and may precipitate as a metal single body on the surface of the negative electrode plate, thereby deteriorating the cycle performance. The embodiments of the present application further combine with a high content of lithium hexafluorophosphate. The mass content of lithium hexafluorophosphate LiPF6 relative to the total mass of the electrolyte is 15% to 20%. The high content of lithium hexafluorophosphate can form a protective layer with lithium fluoride LiF as the main film component on the surface of the positive electrode active material, thereby alleviating the elution of metal elements and non-metal elements to a certain extent and further improving the cycle performance of the lithium-ion battery.
[0041] When the mass content of lithium hexafluorophosphate is less than 15%, the protection performance for the surface of the positive electrode active material weakens. Therefore, it is necessary to adjust the mass content of lithium hexafluorophosphate to 15% or more. When the mass content of lithium hexafluorophosphate is greater than 20%, the viscosity of the electrolyte is significantly increased, which is disadvantageous for the movement of lithium ions from the bulk inside of the negative electrode active material to the surface, slows down the movement speed of lithium ions from the negative electrode surface to the positive electrode surface, is disadvantageous for the movement of lithium ions from the surface of the negative electrode active material to the bulk of the negative electrode active material, and is disadvantageous for the improvement of the cycle performance. Therefore, it is necessary to adjust the mass content of lithium hexafluorophosphate to 20% or less. Exemplarily, the mass content of lithium hexafluorophosphate relative to the total mass of the electrolyte may be 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20% or a range consisting of any two of the above numerical values.
[0042] [Positive electrode plate] In some embodiments, the positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector and containing a positive electrode active material. For example, the positive electrode current collector has two opposing surfaces in its thickness direction, and the positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.
[0043] The positive electrode active material contains a compound with the molecular formula Li d Ni a Co b Mn c M (1-a-b-c) Q z where 0 < d ≦ 2.1, 0.6 < a < 1, 0 < b < 1, 0 < c < 1, and 0.6 < a + b + c < 1, 1.8 ≦ z ≦ 3.5. The M element contains at least one element among B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, Ce. The Q element contains at least one element among O, F.
[0044] The positive electrode active material, in addition to containing lithium, further contains nickel, cobalt, manganese and M. The nickel can improve the gram capacity of the positive electrode active material, the cobalt can stabilize the crystal structure of the positive electrode active material, the manganese can improve the structural stability of the entire positive electrode active material, and the M element can improve the stability of the crystal structure of the positive electrode active material.
[0045] In some embodiments, d is 0.01, 0.02, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 109, 109, 1010, 109, 109, 109, 109, 109, 109, 109, 109, 109, 109, 109 3, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, or a range consisting of any two of the above numerical values.
[0046] In some embodiments, a can be 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range consisting of any two of the foregoing values.
[0047] In some embodiments, b is 0.01, 0.02, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range consisting of any two of the above numerical values.
[0048] In some embodiments, c is 0.01, 0.02, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range consisting of any two of the above numerical values.
[0049] In some embodiments, a+b+c can be 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, or a range consisting of any two of the foregoing values.
[0050] In some embodiments, z can be 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, or a range consisting of any two of the foregoing values.
[0051] Lithium ion batteries involve the release and consumption of active ions, such as Li, during the charging and discharging process, and lithium ion batteries have different molar contents of Li when discharged to different states. In the enumeration of the positive electrode active materials in the embodiments of the present application, the molar content of Li is the initial state of the material, i.e., the state before input, and the positive electrode active material may change in molar content of Li after being applied to a battery system and undergoing charging and discharging cycles.
[0052] In the enumeration of the positive electrode active material in the embodiments of the present application, the molar content of oxygen O is only a theoretical state value, and crystal lattice oxygen release causes a change in the molar content of oxygen O, and in reality, the molar content of oxygen O fluctuates.
[0053] In some embodiments, the M element includes at least one element selected from the group consisting of titanium (Ti) and zirconium (Zr), and optionally M includes Ti and Zr elements. Both Ti and Zr can stabilize the structure of the positive electrode active material, thereby improving the cycle performance. In particular, when M includes both Ti and Zr elements, the two elements can be used in combination to further stabilize the material structure and improve the cycle performance.
[0054] In some embodiments, the total mass content of Ti and Zr elements is 1600 ppm to 3150 ppm based on the total mass of the positive electrode active material. When the amount of Ti and Zr elements added is within the above range, the crystal structure of the positive electrode active material can be further improved, and the cycle performance can be improved.
[0055] The total mass content of Ti and Zr elements is the ratio of the total mass of Ti and Zr elements to the total mass of the positive electrode active material.
[0056] Exemplarily, the total mass content of Ti and Zr elements may be 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm, 2100 ppm, 2200 ppm, 2300 ppm, 2400 ppm, 2500 ppm, 2600 ppm, 2700 ppm, 2800 ppm, 2900 ppm, 3000 ppm, 3100 ppm, 3150 ppm, or a range consisting of any two of the above values.
[0057] In some embodiments, the mass content of Ti element based on the total mass of the positive electrode active material may be 100 ppm to 600 ppm, for example, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 450 ppm, 500 ppm, 600 ppm, or a range consisting of any two of the above values.
[0058] In some embodiments, based on the total mass of the positive electrode active material, the mass content of Zr element is 500 ppm to 2550 ppm, and optionally 1500 ppm to 2550 ppm, for example, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, 1500 ppm, 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm, 2100 ppm, 2200 ppm, 2300 ppm, 2400 ppm, 2500 ppm, 2550 ppm, or a range consisting of any two of the above numerical values.
[0059] In some embodiments, the electrolyte comprises a first additive, and the first additive comprises at least one of lithium difluoro(oxalato)borate LiDFOB and lithium tetrafluoroborate LiBF4. In the later cycle of the lithium ion battery, metal ions, such as Ti and Zr ions, in the positive electrode active material have a risk of dissolving into the electrolyte and migrating to the surface of the negative electrode plate; the first additive comprises fluorine ions and boron ions, which have a relatively strong binding ability with the metal ions, and can reduce the risk of the metal ions migrating to the surface of the negative electrode plate, and can improve the cycle performance of the lithium ion battery; and Ti and Zr ions can improve the stability of the material structure, but can adversely affect the conduction in the crystal lattice of lithium ions, causing power degradation; the first additive can also compensate for the power degradation caused by Ti and Zr ions.
[0060] In some embodiments, the cathode active material comprises a single crystal particle, the single crystal particle comprising an inner region and an outer region, the outer region being a region extending 500 nm from any point on an outer surface of the single crystal particle directly into the interior of the single crystal particle, and the M element comprises aluminum Al, the aluminum Al being distributed in at least the outer region.
[0061] The inner region of the single crystal particle may be understood as the core of the single crystal particle, the outer region covers the outside of the inner region, and there may be no clear boundary between the outer region and the inner region, and the outer region and the inner region may be considered as two artificially defined regions, the outer region is a region where any point on the outer surface of the single crystal particle extends 500 nm toward the inside of the single crystal particle, and the extension path is a straight path, and the outer region may be understood as a ring structure, and the radial spacing of the ring structure is 500 nm or less.
[0062] The aluminum Al element is distributed at least in the outer region, which is useful for forming aluminum oxide Al2O3 in the positive electrode active material, which can passivate the side reaction between the positive electrode active material and the electrolyte, further improve the stability of the positive electrode active material structure, and improve the cycle performance of the lithium ion battery. Of course, in addition to the Al element being distributed in the outer region, the Al element may also be distributed in the inner region.
[0063] In some embodiments, based on the total mass of the positive electrode active material, the mass content of Al element is 500 ppm to 3000 ppm, optionally 1000 ppm to 2000 ppm.
[0064] For example, the mass content of Al element may be 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, 1500 ppm, 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm, or a range consisting of any two of the above numerical values.
[0065] In some embodiments, the electrolyte includes a second additive, and the second additive includes lithium difluorophosphate LiPO2F2. The lithium difluorophosphate LiPO2F2 can be combined with the Al element in the positive electrode active material to improve the DCR of the surface of the positive electrode active material and enhance the interfacial power.
[0066] In some embodiments, the M element further comprises at least one of phosphorus P, sulfur S, and boron B, where at least one of the B, P, and S elements is distributed in the outer region.
[0067] Optionally, the M element includes phosphorus P, sulfur S and boron B. The phosphorus P, sulfur S and boron B elements are absorbed into the oxygen layer to stabilize lithium, thereby improving the stability of the positive electrode active material structure and improving the cycle performance of the lithium ion battery.
[0068] In some embodiments, based on the total mass of the positive electrode active material, the total mass content of the P, S and B elements is 0 to 800 ppm, optionally 10 ppm to 500 ppm, for example, 0, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 80 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, or a range consisting of any two of the above values. When the total mass content of the P, S and B elements is 0, it means that such elements are not added.
[0069] In some embodiments, the total mass content of the P element based on the total mass of the positive electrode active material may be 10 ppm to 500 ppm, for example, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 80 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, or a range consisting of any two of the above numerical values.
[0070] In some embodiments, the total mass content of the S element based on the total mass of the positive electrode active material may be 10 ppm to 500 ppm, for example, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 80 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, or a range consisting of any two of the above numerical values.
[0071] In some embodiments, the total mass content of the B element based on the total mass of the positive electrode active material may be 10 ppm to 500 ppm, for example, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 80 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, or a range consisting of any two of the above numerical values.
[0072] In some embodiments, the electrolyte solution includes a third additive, the third additive including lithium fluorosulfonate, which can form a low resistance film component on the surface of the positive electrode active material, and the third additive can combine with the phosphorus P, sulfur S, and boron B elements in the positive electrode active material to reduce the DCR on the surface of the positive electrode active material and improve the interfacial power.
[0073] In the embodiment of the present application, the content of elements in the positive electrode active material is a meaning known in the art, and can be detected using instruments and methods known in the art. For example, referring to EPA 6010D-2014, it is tested by inductively coupled plasma atomic emission spectroscopy and measured using plasma atomic emission (ICP-OES, instrument model number: Thermo ICAP7400). First, 0.4 g of the positive electrode active material is weighed, and 10 ml of aqua regia (50% concentration) is added thereto. Then, it is placed on a plate at 180 ° C for 30 minutes. After decomposition on the plate, the volume is fixed to 100 mL, and a quantitative test is performed using the standard curve method.
[0074] In some embodiments, the positive electrode film layer further optionally includes a positive electrode conductive agent. The embodiments of the present application are not particularly limited to the type of the positive electrode conductive agent, and for example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, based on the total mass of the positive electrode film layer, the mass content of the positive electrode conductive agent is ≦5%.
[0075] In some embodiments, the positive electrode membrane layer further optionally includes a positive electrode adhesive. The embodiments of the present application are not particularly limited to the type of the positive electrode adhesive, and for example, the positive electrode adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. In some embodiments, based on the total mass of the positive electrode membrane layer, the mass content of the positive electrode adhesive is ≦5%.
[0076] In some embodiments, the ratio of the packing density of the positive electrode membrane layer to the packing density of the negative electrode membrane layer is (2 to 2.5): 1. For example, it may be 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, or a range consisting of any two of the foregoing values.
[0077] In some embodiments, the packed density PD of the positive electrode membrane layer is 3.0 g / cm 3 to 3.5 g / cm 3 Optionally, 3.2 g / cm 3 to 3.5 g / cm 3 For example, 3 g / cm 3 , 3.1g / cm 3 , 3.2g / cm 3 , 3.3g / cm 3 , 3.35g / cm 3 , 3.4g / cm 3 , 3.5g / cm 3 Or, it may be a range consisting of any two of the above values.
[0078] In the embodiment of the present application, the compaction density of the positive electrode active material layer is a meaning known in the art, and can be tested by a method known in the art. For example, take a positive electrode plate after one side is coated and cold pressed (if it is a positive electrode plate coated on both sides, the positive electrode film on one side may be wiped off first), punch it into a small disk with an area of S1, weigh it, and record it as M1. Next, wipe off the positive electrode film of the positive electrode plate after the above weighing, weigh the weight of the positive electrode current collector, and record it as M0, where the areal density of the positive electrode active material layer=(weight of the positive electrode plate M1-weight of the positive electrode current collector M0) / S1, and the compaction density of the positive electrode active material layer=area density of the positive electrode active material layer / thickness of the positive electrode active material layer.
[0079] In some embodiments, the positive electrode current collector may employ a metal foil sheet or a composite current collector. An example of the metal foil sheet may employ aluminum foil. The composite current collector may include a polymeric base layer and a metal material layer formed on at least one surface of the polymeric base layer. For example, the metal material of the metal material layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymeric base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0080] In some embodiments, the thickness of the positive electrode current collector is less than or equal to 10 μm, optionally between 8 μm and 10 μm.
[0081] The thickness of the positive electrode current collector is relatively thin, which can weaken the heat dissipation path of the lithium ion battery and can retain some of the heat in the lithium ion battery in a low SOC discharge state, which is favorable for improving the DCR at low SOC, and thereby improving the discharge power at low SOC.
[0082] For example, the thickness of the positive electrode current collector may be 8 μm, 8.2 μm, 8.5 μm, 8.8 μm, 9.0 μm, 9.2 μm, 9.5 μm, 9.6 μm, 9.8 μm, 10 μm, or a range consisting of any two of the above values.
[0083] In the embodiment of the present application, the thickness of the positive electrode current collector has a meaning known in the art and can be detected using an instrument and a method known in the art, for example, by taking a positive electrode plate as a sample, then cleaning the positive electrode film layer on the surface of the positive electrode plate with an organic solvent such as alcohol, and measuring the thickness of the positive electrode current collector with a micrometer.
[0084] The positive electrode film layer is generally obtained by applying a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is generally formed by dispersing a positive electrode active material, an optional conductive agent, an optional adhesive, and any other components in a solvent and stirring the mixture uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).
[0085] [Electrolyte] Organic solvents In some embodiments, the electrolyte further comprises an organic solvent.
[0086] In some embodiments, the organic solvent may include a cyclic carbonate, and the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate, based on the total mass of the electrolyte, is (0.60 to 2.50):1, optionally (1.00 to 1.65):1.
[0087] The estimated beneficial effects are as follows: When the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate is within the above range, it is favorable for sufficiently dissociating more lithium ions from the lithium hexafluorophosphate, so that even at the end of discharge with a low SOC, more lithium ions can be contained in the electrolyte system, and the lithium ions can be continuously dissociated with the progress of the battery reaction, improving the power performance of the battery.
[0088] For example, the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate based on the total mass of the electrolyte may be 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.15:1, 1.2:1, 1.25:1, 1.3:1, 1.35:1, 1.37:1, 1.4:1, 1.5:1, 1.6:1, 1.65:1, 1.67:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, or a range consisting of any two of the above values.
[0089] In some embodiments, the mass content of the cyclic carbonate is 10% to 45%, and more preferably 20% to 30%, based on the total mass of the electrolyte solution. The cyclic carbonate has a high dielectric constant and a high ionic conductivity, and can form a stable SEI film on the surface of the negative electrode active material.
[0090] For example, based on the total mass of the electrolyte, the mass content of the cyclic carbonate may be 10%, 10.92%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 20.93%, 21%, 22%, 23%, 23.66%, 24%, 25%, 26%, 27%, 28%, 29%, 29.12%, 30%, 30.03%, 31%, 32%, 33%, 34%, 35%, 36%, 36.4%, 37%, 38%, 39%, 40%, 40.4%, 41%, 42%, 43%, 44%, 45%, or a range consisting of any two of the above values.
[0091] In some embodiments, the cyclic carbonate may include at least one of ethylene carbonate EC, propylene carbonate PC, and butylene carbonate BC.
[0092] In some embodiments, the organic solvent may include a linear carbonate, and the ratio of the mass content of the linear carbonate to the mass content of the cyclic carbonate based on the total mass of the electrolyte is (0.9 to 6): 1, and optionally (1.5 to 2.65): 1. When the ratio of the mass content of the linear carbonate to the mass content of the cyclic carbonate satisfies the above range, the viscosity and ionic conductivity of the electrolyte can be improved at the same time, and the kinetic performance of the lithium ion can be improved.
[0093] Exemplary ratios of the mass content of cyclic carbonate to the mass content of linear carbonate are 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.37:1, 1.4:1, 1.5:1, 1.6:1, 1.65:1, 1.67:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3.0:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 3.10:1, 3.20:1, 3.35:1, 3.40:1, 3.50:1, 3.65:1, 3.70:1, 3.85:1, 3.90:1, 3.9 ... :1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4.0:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1, 5.0:1, 5.1:1, 5.2:1, 5.3:1, 5.4:1, 5.5:1, 5.6:1, 5.7:1, 5.8:1, 5.9:1, 5.95:1, 6:1, or a range consisting of any two of the above numerical values.
[0094] In some embodiments, the mass content of the linear carbonate is 35% to 75%, and more preferably 50% to 75%, based on the total mass of the electrolyte. The viscosity of the linear carbonate is relatively low, which is favorable for the rapid migration of lithium ions, and the electrochemical stability is higher, and the low temperature performance of the electrolyte can be improved.
[0095] For example, based on the total mass of the electrolyte, the mass content of the linear carbonate may be 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 50.4%, 51%, 52%, 52.5%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 68%, 70%, 71%, 72%, 73%, 74%, 75%, or a range consisting of any two of the above values.
[0096] In some embodiments, the linear carbonate comprises at least one of ethyl methyl carbonate, EMC, diethyl carbonate, DEC, and dimethyl carbonate, DMC.
[0097] Additives In some embodiments, the electrolyte may further include an additive.
[0098] In some embodiments, the additive comprises a first additive comprising at least one of lithium difluoro(oxalato)borate LiDFOB and lithium tetrafluoroborate LiBF4. In the later cycle of a lithium ion battery, metal ions, such as Ti and Zr ions, in the positive electrode active material have a risk of dissolving into the electrolyte and migrating to the surface of the negative electrode plate, and the first additive comprises fluorine ions and boron ions, which have a relatively strong binding ability with the metal ions, and can reduce the risk of the metal ions migrating to the surface of the negative electrode plate, improve the cycle performance of the lithium ion battery, and can also compensate for the deterioration of power caused by Ti and Zr ions.
[0099] In some embodiments, based on the total mass of the electrolyte, the mass content of the first additive is 30 ppm to 1200 ppm, optionally 100 ppm to 400 ppm, the mass content of Ti combined with the mass content of Zr element is 100 ppm to 600 ppm, and the mass content of Zr element is 500 ppm to 2550 ppm, and the first additive can improve the binding ability of Ti and Zr ions, and further improve the cycle performance of the lithium ion battery.
[0100] Exemplarily, the mass content of the first additive is 30 ppm, 35 ppm, 40 ppm, 45 ppm, 50 ppm, 60 ppm, 70 ppm, 80 ppm, 90 ppm, 100 ppm, 110 ppm, 120 ppm, 130 ppm, 140 ppm, 150 ppm, 160 ppm, 170 ppm, 180 ppm, 190 ppm, 200 ppm, 210 ppm, 220 ppm, 230 ppm, 240 ppm, 250 ppm, 260 ppm, 270 ppm, 280 ppm, 290 ppm, 300 ppm , 310 ppm, 320 ppm, 330 ppm, 340 ppm, 350 ppm, 360 ppm, 370 ppm, 380 ppm, 390 ppm, 400 ppm, 410 ppm, 420 ppm, 430 ppm, 440 ppm, 450 ppm, 460 ppm, 470 ppm, 480 ppm, 490 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, or a range consisting of any two of the above numerical values.
[0101] In some embodiments, the additive comprises a second additive comprising lithium difluorophosphate LiPO2F2. Lithium difluorophosphate LiPO2F2 can form a membrane layer rich in inorganic components on the surface of the positive electrode active material, which is favorable for improving the ion conduction and electronic conduction performance of the membrane layer, and the interface ion resistance of the formed membrane layer is relatively low, which is favorable for the transport of lithium ions, and can improve the DCR at low SOC; in particular, lithium difluorophosphate can be combined with the Al element in the positive electrode active material to improve the DCR of the surface of the positive electrode active material and improve the interface power.
[0102] In some embodiments, based on the total mass of the electrolyte, the mass content of the second additive is 100 ppm to 3000 ppm, and optionally 1000 ppm to 2000 ppm. The second additive with the above mass content can be combined with 500 ppm to 3000 ppm of Al element, which can better improve the DCR of the surface of the positive electrode active material and improve the interfacial power.
[0103] Exemplarily, the mass content of the second additive may be 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1400 ppm, 1500 ppm, 1600 ppm, 1700 ppm, 1800 ppm, 1900 ppm, 2000 ppm, 2100 ppm, 2200 ppm, 2300 ppm, 2400 ppm, 2500 ppm, 2600 ppm, 2700 ppm, 2800 ppm, 2900 ppm, 3000 ppm, or a range consisting of any two of the above numerical values.
[0104] In some embodiments, the additive comprises a third additive, the third additive comprises lithium fluorosulfonate, the third additive can form a membrane layer rich in inorganic components on the surface of the positive electrode active material, which is favorable for improving the ion conduction and electron conduction performance of the membrane layer, and the interfacial ion resistance of the formed membrane layer is relatively low, which is favorable for the transport of lithium ions, and can improve the DCR at low SOC, in particular, lithium difluorophosphate can be combined with phosphorus P, sulfur S and boron B elements in the positive electrode active material to improve the DCR of the surface of the positive electrode active material and improve the interfacial power.
[0105] Exemplarily, the lithium fluorosulfonate may include at least one of lithium trifluoromethanesulfonate and lithium perfluorohexanesulfonate.
[0106] In some embodiments, based on the total mass of the electrolyte, the mass content of the third additive is 50 ppm to 200 ppm. The third additive of the above mass content can be combined with 10 ppm to 800 ppm of phosphorus P, sulfur S and boron B elements, which can better improve the DCR of the surface of the positive electrode active material and improve the interfacial power.
[0107] Exemplarily, the mass content of the third additive may be 50 ppm, 60 ppm, 70 ppm, 80 ppm, 90 ppm, 100 ppm, 200 ppm, or a range consisting of any two of the above numerical values.
[0108] In some embodiments, the additive comprises a fourth additive, and the fourth additive may further comprise at least one of 1,3-propane sultone PS, vinylene carbonate VC, and lithium fluorosulfonate LiSO3F.
[0109] In some embodiments, based on the total mass of the electrolyte, the ratio of the mass content of 1,3-propane sultone PS, the mass content of vinylene carbonate VC, and the mass content of lithium fluorosulfonate LiSO3F is (0.050 to 0.300):(0.100 to 0.500):(0.001 to 0.300). The mass content of one component in the additive is 0, indicating that this component is not added to the electrolyte. When the ratio of the mass content of 1,3-propane sultone PS, the mass content of vinylene carbonate VC, and the mass content of lithium fluorosulfonate LiSO3F is within the above range, the above component can essentially participate in forming an SEI film on the surface of the negative electrode active material, and the SEI film can effectively mitigate the expansion of the silicon-based material.
[0110] In some embodiments, the mass content of 1,3-propane sultone PS based on the total mass of the electrolyte may be 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or a range consisting of any two of the above values.
[0111] In some embodiments, the mass content of vinylene carbonate VC based on the total mass of the electrolyte solution may be 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or a range consisting of any two of the above values.
[0112] In some embodiments, the mass content of lithium fluorosulfonate LiSO3F based on the total mass of the electrolyte solution may be 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, or a range consisting of any two of the foregoing values.
[0113] In some embodiments, the additive may include fluorinated cyclic carbonate, which can participate in the formation of SEI film on the surface of the negative electrode active material, and can effectively protect the negative electrode active material, and the fluorinated cyclic carbonate has a certain desolvation ability, is favorable to the migration of lithium ions, and can improve the DCR at low SOC and improve the discharge power.
[0114] In some embodiments, the fluorinated cyclic carbonate includes at least one of monofluoroethylene carbonate FEC, bisfluoroethylene carbonate DFEC, and trifluoropropylene carbonate TFPC, and optionally, the fluorinated cyclic carbonate includes monofluoroethylene carbonate FEC. FEC contains a relatively small number of fluorine atoms, has a stronger polarity, and is more likely to be released and participate in the film-forming reaction of the SEI film.
[0115] In some embodiments, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of elemental silicon relative to the total mass of the electrolyte is (0.5 to 9.5): 1, optionally (1 to 2): 1. Illustratively, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of elemental silicon relative to the total mass of the electrolyte is 0.5: 1, 0.6: 1, 0.7: 1, 0.8: 1, 0.9: 1, 1: 1, 1.05: 1, 1.1: 1, 1.2: 1, 1.3: 1, 1.35: 1, 1.4: 1, 1.5: 1, 1.57: 1, 1.6: 1, 1.7: 1, 1.8: 1, 1.9: 1, 2: 1, 2.1: 1, 2.2: 1, The ratio may be 2.3:1, 2.36:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 4.7:1, 4.71:1, 4.8:1, 5:1, 5.5:1, 5.8:1, 6:1, 6.5:1, 7:1, 7.5:1, 7.8:1, 8:1, 8.5:1, 9:1, 9.1:1, 9.2:1, 9.3:1, 9.4:1, 9.43:1, 9.5:1, or a range consisting of any two of the above values.
[0116] Fluorinated cyclic carbonate can participate in the formation of SEI film on the surface of negative electrode active material, improve the film components and properties, and effectively protect the negative electrode active material; especially when the negative electrode contains silicon, the film composition of SEI film formation needs to be further optimized due to the property of silicon expanding; the optimization of the film composition is adjusted by adjusting the relative ratio of film-forming additives in the electrolyte, and the fluorinated cyclic carbonate can participate in the film formed to improve the flexibility of the SEI film, and can improve the structural collapse caused by silicon releasing a large amount of lithium ions in a short time at the end of discharge; and the fluorinated cyclic carbonate has a certain desolvation ability, which is favorable for the migration of lithium ions, and can improve the DCR at low SOC and improve the discharge power. Through research, it has been found that when the content ratio of silicon in the negative electrode active material and FEC in the electrolyte meets (0.5 to 9.5):1, the rate performance of the battery at the end of discharge is significantly improved.
[0117] In some embodiments, the mass content of the fluorinated cyclic carbonate relative to the total mass of the electrolyte may be 0.95% to 5.8%, and optionally 1.5% to 3%, for example, 0.95%, 0.98%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 1.91%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9 ...3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6 %, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.82%, 3.9%, 4%, 4.1%, 4.5%, 5%, 5.2%, 5.5%, 5.7%, 5.73%, 5.8%, or a range consisting of any two of the above numbers.
[0118] Lithium salts After being dissolved in an organic solvent, the lithium salt can release a large amount of active lithium ions to participate in charging and discharging.
[0119] In some embodiments, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt is (0.05 to 0.30): 1, and optionally (0.10 to 0.20): 1, based on the total mass of the electrolyte. The fluorinated cyclic carbonate can form an organic substance on the surface of the silicon-based material, and improve the flexibility of the SEI film; the lithium salt can participate in the formation of the SEI film, and the SEI film contains an inorganic component, which is favorable for improving the ionic and electronic conductivity performance of the SEI film, and can improve the ionic and electronic conductivity performance of the entire negative electrode plate; when the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt is within the above range, the flexibility of the SEI film, the ionic and electronic conductivity performance are improved, and the DCR can be reduced to improve the discharge power of the lithium ion battery.
[0120] Exemplarily, the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the lithium salt may be 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.10:1, 0.11:1, 0.12:1, 0.13:1, 0.14:1, 0.15:1, 0.16:1, 0.17:1, 0.18:1, 0.19:1, 0.20:1, 0.21:1, 0.22:1, 0.23:1, 0.24:1, 0.25:1, 0.26:1, 0.27:1, 0.28:1, 0.29:1, 0.30:1, or a range consisting of any two of the above values.
[0121] In some embodiments, the lithium salt further comprises at least one of inorganic phosphate and inorganic borate, and optionally the lithium salt comprises fluorine-containing inorganic borate.The inorganic phosphate and inorganic borate can participate in the formation of inorganic components in the SEI film, which is beneficial to improve the conductive ion and electron conductive performance of the SEI film, and the interface ionic resistance of the formed SEI film is low, which is beneficial to the transport of lithium ions, and can improve the DCR at low SOC.
[0122] In some embodiments, the inorganic phosphate comprises at least one of lithium monofluorophosphate Li2PO3F and lithium difluorophosphate LiPO2F2, and optionally, the inorganic phosphate comprises lithium difluorophosphate LiPO2F2.
[0123] In some embodiments, the borate salt comprises at least one of lithium tetrafluoroborate LiBF4, lithium difluoro(oxalato)borate LiDFOB, and lithium bis(oxalato)borate.
[0124] In some embodiments, based on the total mass of the electrolyte, the total mass content of inorganic phosphates and inorganic borates is 0.05% or more and 0.50% or less, optionally 0.10% to 0.30%.
[0125] For example, the total mass content of inorganic phosphate and inorganic borate may be 0.05%, 0.06%, 0.08%, 0.1%, 0.15%, 0.18%, 0.2%, 0.22%, 0.25%, 0.28%, 0.3%, 0.32%, 0.35%, 0.38%, 0.4%, 0.42%, 0.45%, 0.48%, 0.5%, or a range consisting of any two of the above values.
[0126] Exemplary lithium salts include lithium tetrafluoroborate LiBF4, lithium difluoro(oxalato)borate LiDFOB, and lithium bis(oxalato)borate.
[0127] Optionally, based on the total mass of the electrolyte, the mass content of lithium tetrafluoroborate LiBF4 may be 0.01% to 0.2%, for example, 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, or a range consisting of any two of the above values.
[0128] Optionally, based on the total mass of the electrolyte, the mass content of lithium difluoro(oxalato)borate LiDFOB may be 0.01% to 0.1%, for example, 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, or a range consisting of any two of the above values.
[0129] Optionally, based on the total mass of the electrolyte, the mass content of lithium bis(oxalato)borate may be 0.01% to 0.5%, for example, 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, or a range consisting of any two of the above values.
[0130] The qualitative and quantitative determination of each substance or element in this application can be detected using appropriate devices and methods known to those skilled in the art, and the relevant detection methods can refer to detection standards at home and abroad, enterprise standards at home and abroad, etc., and those skilled in the art can adaptively change some detection steps / instrument parameters, etc. from the perspective of detection accuracy to obtain more accurate detection results. Qualitative or quantitative determination can be performed using one detection method, or multiple detection methods can be combined to perform qualitative or quantitative measurement.
[0131] In the embodiment of the present application, the type and content of the concentration of inorganic components / lithium salts in the electrolyte are the meanings known in the art, and can be detected using instruments and methods known in the art, for example, the concentration of inorganic components / lithium salts in the electrolyte can be analyzed qualitatively or quantitatively by ion chromatography analysis method with reference to standard JY / T020-1996 "General Rules for Ion Chromatography Analysis Method". In the embodiment of the present application, a newly manufactured electrolyte can be used as a sample, or a battery that has already been discharged (discharged to the lower cutoff voltage and the charge state of the battery is about 0% SOC) can be disassembled in the reverse direction, and the free electrolyte obtained from the battery can be used as a sample for detection using ion chromatography analysis method.
[0132] In the embodiment of the present application, the type and content of organic components in the electrolyte are the meanings known in the art, and can be detected using instruments and methods known in the art, for example, the organic components in the electrolyte can be qualitatively and quantitatively analyzed by gas chromatography with reference to GB / T9722-2006 "General Rules for Gas Chromatography of Chemical Reagents". In the embodiment of the present application, a newly manufactured electrolyte can be used as a sample, or a discharged battery (discharged to a lower cutoff voltage and the charge state of the battery is about 0% SOC) can be reversely disassembled, and the free electrolyte obtained from the battery can be used as a sample for detection using ion chromatography analysis.
[0133] Further, for example, the components of a certain additive in an electrolyte are tested by liquid-phase nuclear magnetic resonance (NMR) to detect lithium difluorophosphate and lithium hexafluorophosphate. In a nitrogen gas glove box, a 7 ml glass bottle is prepared, 5 ml of nuclear magnetic reagent premix is added to the glass bottle, and the bottle is left to stand for 24 h at room temperature 20-25 ° C in a nitrogen atmosphere glove box, allowing the electrolyte in the electrode plate and separator to diffuse into the nuclear magnetic premix, thereby obtaining a nuclear magnetic test sample. The nuclear magnetic premix contains 100 ml of deuterated acetonitrile and 3 ml of trifluoromethylbenzene CF3ph, and the above nuclear magnetic reagent premix is dried in advance with molecular sieve 4A (100 ml of nuclear magnetic reagent premix is added to 15 g of freshly opened 4A molecular sieve and dried at room temperature 20-25 ° C in a nitrogen gas glove box for more than 30 days). Measurement was performed using 19F NMR (nuclear magnetic (NMR): Bruker Avance 400HD).
[0134] To identify and quantify each species, the following settings were used in flip angle and scan time:
[0135] Fluorine spectrum test pulse sequence: 2gfhigqn.2, Delay time: 1 second, Number of scans: 16, The relative contents of trifluoromethylbenzene and LiPF6 are calculated based on the signal peak integral intensity of the two substances in F-NMR. The calculation method is: PF6 - Relative content = (I PF6 - ×M PF6 - / 6) / (I CF3ph ×M CF3ph / 3), where I is the corresponding nuclear magnetic peak area, and M is the corresponding relative molecular mass. Then calculate the content of lithium hexafluorophosphate in the electrolyte based on the molar ratio relationship between hexafluorophosphate and lithium ions.
[0136] The content of the deuteration reagent in the electrolyte is calculated based on the content of lithium hexafluorophosphate LiPF6.
[0137] Trifluoromethylbenzene and PO2F2 in F-NMR - Calculate the relative content of the two substances based on the integrated intensity of the signal peaks of the two substances. The calculation method is as follows: PO2F2 - Relative content = (I PO2F2- ×M PO2F2- / 2) / (I CF3ph ×M CF3ph / 3), where I is the corresponding nuclear magnetic peak area, and M is the corresponding relative molecular mass. Then calculate the content of lithium difluorophosphate in the electrolyte based on the molar ratio relationship between difluorophosphate and lithium ion.
[0138] In some embodiments, the lithium ion battery has a retention factor of 1.0 g / Ah to 2.5 g / Ah, optionally 1.8 g / Ah to 2.2 g / Ah.
[0139] The liquid retention coefficient of a lithium ion battery can reflect the liquid retention capacity of the electrolyte. When the liquid retention coefficient of a lithium ion battery is within the above range, the electrolyte can have good infiltration effect on the positive and negative electrodes, and has a certain gap between the negative electrode and the separator, which can provide an expansion space for the volume expansion of the silicon-based material, thereby reducing the risk of the entire battery expanding.
[0140] In some embodiments, the lithium ion battery has a retention factor of 1.0 g / Ah to 2.5 g / Ah, optionally 1.8 g / Ah to 2.2 g / Ah.
[0141] In some embodiments, the various solutes or solvents in the electrolyte solutions referred to in this application include not only substances that are actively added when producing the electrolyte solution, but also substances that are derived from substances already present in one / some electrolyte solutions during the production of the electrolyte solution or during the production of a battery from said electrolyte solution or during the storage or use of a battery containing said electrolyte solution.
[0142] The liquid retention coefficient of a lithium ion battery can reflect the liquid retention capacity of the electrolyte. When the liquid retention coefficient of a lithium ion battery is within the above range, the electrolyte can have good infiltration effect on the positive electrode plate and the negative electrode plate, and has a certain gap between the negative electrode plate and the separator, which can provide an expansion space for the volume expansion of the silicon-based material, thereby reducing the risk of the entire lithium ion battery expanding.
[0143] For example, the electrolyte retention coefficient of a lithium ion battery may be 1.0 g / Ah, 1.1 g / Ah, 1.2 g / Ah, 1.3 g / Ah, 1.4 g / Ah, 1.5 g / Ah, 1.6 g / Ah, 1.7 g / Ah, 1.8 g / Ah, 1.9 g / Ah, 2.0 g / Ah, 2.1 g / Ah, 2.2 g / Ah, 2.3 g / Ah, 2.4 g / Ah, 2.5 g / Ah, or a range consisting of any two of the above values.
[0144] In the embodiment of the present application, the liquid retention coefficient of the lithium ion battery has a meaning known in the art and can be detected by using instruments and methods known in the art, for example, according to GB / T 31486-2015 "Electrical performance requirements and test methods for power storage batteries for electric vehicles", at 25°C, the lithium ion battery is charged at 1C to 4.35V, then discharged at 1C to 2.8V, and the discharged capacity C is obtained as the denominator, the lithium ion battery is weighed and represented as M0, and then the positive electrode plate, the negative electrode plate, the separator and the electrolyte are disassembled, where the free electrolyte is present in the housing / bag, and all the above solid assemblies are placed in an oven at 60°C and baked for more than 4 hours (including but not limited to the positive electrode plate, the negative electrode plate, the separator, and other mechanical parts of the disassembled lithium ion battery that contribute to M0), and then the entire assembly of the lithium ion battery is weighed and represented as M1, where the weight difference between M0 and M1 is the numerator. The liquid retention coefficient is equal to the volume C divided by the weight difference between M0 and M1.
[0145] [Negative electrode plate] In some embodiments, the lithium ion battery further comprises a negative plate.
[0146] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces facing each other in a thickness direction thereof, and the negative electrode film layer is disposed on either one or both of the two facing surfaces of the negative electrode current collector.
[0147] In some embodiments, the negative electrode membrane layer comprises a negative electrode active material including elemental carbon and elemental silicon, and the ratio of the mass content of the elemental silicon to the mass content of the elemental carbon, based on the total mass of the negative electrode active material, is from (0.3:99.7) to (3:97).
[0148] The negative electrode active material of the lithium ion battery includes a carbon-based material that provides a carbon element and a silicon-based material that provides a silicon element, and the carbon-based material that provides the carbon element may contain a carbon element, may simultaneously contain a silicon element, or may of course contain only a carbon element, and the silicon-based material that supplies the silicon element may contain a silicon element, may simultaneously contain a carbon element, or may of course contain only a silicon element. The negative electrode active material also includes a carbon-based material and a silicon-based material, and since the lithium release voltage plateau of the silicon-based material is relatively high compared to the carbon-based material, even at a low SOC (for example, SOC≦10%), the silicon-based material can still continue to participate in discharging, which makes up for the shortcomings of the carbon-based material that is difficult to discharge / cannot continue discharging at a low SOC, improves the direct current internal resistance DCR during the discharge process of the battery, and further improves the power performance during the discharge process of the battery.
[0149] The mass content of silicon element is adjusted to a smaller content, and the reasons are as follows: although the lithium release potential of silicon-based materials is higher than that of carbon-based materials, the volume expansion or contraction is relatively large during charging and discharging, which may cause defects such as structural collapse, bursting, and powdering of the negative electrode active material, and further cause undesirable side reactions inside the battery. In addition, the electrical conductivity of silicon-based materials themselves is relatively poor, and a content that is too high is disadvantageous to improving DCR, so that, under other conditions, the power performance of a battery corresponding to a negative electrode active material containing a silicon content that is too high is inferior to that of a battery with a lower silicon content.
[0150] The electrolyte of the embodiment of the present application further uses 15% to 20% lithium hexafluorophosphate in combination, and the electrolyte cooperates with the negative electrode to improve the power performance of the battery at the end of discharge.
[0151] Lithium hexafluorophosphate can participate in the formation of a solid electrolyte interphase (SEI) film component on the surface of the negative electrode active material, and lithium hexafluorophosphate with a high fluorine atom ratio can optimize the SEI film component, and the improving effect of lithium hexafluorophosphate with a high mass content on the SEI film component is more significant, improving the ratio of lithium fluoride (e.g. lithium fluoride) in the SEI film. Such an SEI film with a relatively high lithium fluoride ratio can, on the one hand, alleviate the problem of the silicon-based material being pulverized and improve the structural stability of the entire negative electrode active material, and on the other hand, delay the side reaction between the electrolyte and the surface of the negative electrode active material, thereby improving the discharge stability of the silicon-based material in the later stage of discharge and further improving the power performance of the battery.
[0152] In addition, in the final stage of discharge at low SOC of the lithium ion battery, the concentration of lithium ions in the negative electrode active material is relatively low, and it is relatively difficult for lithium ions to be desorbed from the negative electrode active material, which reduces the concentration difference of lithium salt in the electrolyte system, improves the internal resistance of the lithium ion battery, and further reduces the discharge power. The electrolyte in the embodiment of the present application contains a high content of lithium hexafluorophosphate, which can contribute more lithium ions to the battery system, improve the concentration of lithium ions in the electrolyte, effectively reduce the concentration polarization of lithium salt, and promote the migration of lithium ions from the negative electrode plate to the positive electrode plate, thereby further improving the power performance of the lithium ion battery.
[0153] The mass content of carbon element relative to the total mass of the negative electrode active material is 97% or more and 99.7% or less, for example, 97%, 97.2%, 97.5%, 97.6%, 97.8%, 98%, 98.2%, 98.5%, 98.6%, 98.8%, 99%, 99.5%, 99.7%, or a range consisting of any two of the above numerical values.
[0154] The mass content of silicon element relative to the total mass of the negative electrode active material is 0.3 to 3.0%, for example, 0.3%, 0.32%, 0.4%, 0.5%, 0.6%, 0.64%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.27%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 1.91%, 2.0%, 2.1%, 2.2%, 2.23%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.86%, 2.9%, 3%, or a range consisting of any two of the above numerical values.
[0155] As described above, the silicon element may be derived from a silicon-based material, and the silicon-based material may be a raw material constituting the negative electrode film layer. In some embodiments, the silicon element contained in the negative electrode active material exists in the negative electrode film layer in at least one form of elemental silicon, a silicon-carbon composite, or silicon oxide SiOx (0 < x ≤ 2). Here, the elemental silicon, the silicon-carbon composite, and the silicon oxide SiOx (0 < x ≤ 2) may refer to a silicon-based material or the form of the silicon element in the negative electrode plate in the battery after formation. For the silicon oxide SiOx here, 0 < x ≤ 2 because the bonding mode between silicon atoms and oxygen atoms in the negative electrode film layer is diverse, and it may be at least one of SiO, SiO 1.2 , or SiO2 and other possible silicon oxides. Here, the silicon-carbon composite may be a silicon-carbon composite formed by a specific chemical reaction between a silicon element and a carbon element in a lithium-ion battery. The voltage plateau of the silicon oxide itself is high, which is advantageous for releasing lithium ions at a low state of charge (SOC). It contributes to the capacity and participates in discharging, improving the power performance of the lithium-ion battery.
[0156] The carbon element is mainly a constituent element of a carbon-based material. In some embodiments, the carbon-based material may include at least one of artificial graphite and natural graphite. Optionally, the carbon-based material may include natural graphite. Natural graphite generally has a smaller particle size, faster lithium-ion release, and its surface generally contains amorphous carbon. The presence of amorphous carbon can reduce the DC resistance (DCR) and improve the power.
[0157] The qualitative and quantitative determination of each substance or element in this application can be detected using appropriate devices and methods known to those skilled in the art. Relevant detection methods can refer to detection standards at home and abroad in China, corporate standards at home and abroad in China, etc. And those skilled in the art can adaptively change some detection steps / instrument parameters from the perspective of detection accuracy to obtain more accurate detection results. It may be qualitatively or quantitatively analyzed using one detection method, or a combination of multiple detection methods may be used for qualitative or quantitative measurement.
[0158] For example, taking the detection of silicon element in the negative electrode active material as an example, qualitative and quantitative analysis may be carried out with reference to JY / T015-1996 "General Rules for Inductively Coupled Plasma Atomic Emission Spectrometric Analysis Methods", and further analysis may be carried out on the surface elements of the negative electrode plate or the cross-sectional elements after ion polishing with reference to the GB-T17359-2012 standard.
[0159] For example, the graphite material in this application can be combined with JIS / K0131-1996 General Rules for X-ray Diffraction Analysis Method to perform X-ray powder diffraction test and qualitative analysis on the negative electrode plate or the negative electrode active material. The silicon single crystal, silicon-carbon composite, and silicon oxide SiOx (0 < x ≤ 2) in this application can also use the above X-ray powder diffraction test and qualitative analysis.
[0160] In some embodiments, based on the total mass of the negative electrode active material, the ratio of the mass content of silicon oxide SiOx (x = 1) to the mass content of artificial graphite is from (0.5:99.5 to (5:95). When the negative electrode active material satisfies the above content range, the discharge power at low SOC can be further improved.
[0161] Exemplarily, the ratio of the mass content of silicon oxide SiO to the mass content of artificial graphite may be 0.5:99.5, 1:99, 1.5:98.5, 2:98, 2.5:97.5, 3:97, 3.5:96.5, 4:96, 4.5:95.5, 5:95 or a range consisting of any two of the above numerical values.
[0162] In some embodiments, the mass content of silicon oxide SiO may be 0.5% to 5%, optionally 2% to 3.5%, e.g., 0.5%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%. , 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5.0%, or a range consisting of any two of the above values. When the mass content of silicon oxide SiO satisfies the above content range, the discharge power at low SOC can be further improved.
[0163] In some embodiments, the mass content of the synthetic graphite may be 95% to 99.5%, optionally 96.5% to 98%, e.g., 95%, 95.1%, 95.2%, 95.3%, 95.4%, 95.5%, 95.6%, 95.7%, 95.8%, 95.9%, 96%, 96.1%, 96.2%, 96.3%, 96.4%, 96.5%, 96.6%, 96.7%, 96.8%, 96.9%, 96.10%, 96.11%, 96.12%, 96.13%, 96.14%, 96.15%, 96.16%, 96.17%, 96.18%, 96.19%, 96.20%, 96.21%, 96.22%, 96.23%, 96.24%, 96.25%, 96.26%, 96.27%, 96.28%, 96.29%, 96.29%, 96.28%, 96.29%, 96.29%, 96.26%, 96.29%, 96.28%, 96.29 ... %, 96.8%, 96.9%, 97%, 97.1%, 97.2%, 97.3%, 97.4%, 97.5%, 97.6%, 97.7%, 97.8%, 97.9%, 98%, 98.1%, 98.2%, 98.3%, 98.4%, 98.5%, 98.6%, 98.7%, 98.8%, 98.9%, 99%, 99.5%, or a range consisting of any two of the above values. When the mass content of the artificial graphite satisfies the above content range, the cycle performance of the battery can be improved.
[0164] In some embodiments, the mass content of the negative electrode active material is 85% or more and less than 100% based on the total mass of the negative electrode membrane layer. For example, the mass content of the negative electrode active material may be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, or a range consisting of any two of the above values.
[0165] In some embodiments, the thickness of the single-sided negative electrode film layer is 65 μm to 90 μm. The thickness of the negative electrode film layer is the thickness of the single-sided negative electrode film layer, for example, when a negative electrode film layer is provided on both sides of the negative electrode current collector, the thickness of the negative electrode film layer on one side of the negative electrode current collector is the thickness of one side of the negative electrode film layer, or when a negative electrode film layer is provided on one side of the both sides of the negative electrode current collector, the thickness of the negative electrode film layer on this side is the thickness of the single-sided negative electrode film layer. When the thickness of the negative electrode film layer is in the above range, the transport speed of lithium ions in the negative electrode plate and the transport speed in the separator can be almost the same, which reduces the risk of worsening concentration polarization and is advantageous for improving discharge performance.
[0166] For example, the thickness of the negative electrode film layer may be 65 μm, 66 μm, 67 μm, 68 μm, 69 μm, 70 μm, 71 μm, 72 μm, 73 μm, 74 μm, 75 μm, 76 μm, 77 μm, 78 μm, 79 μm, 80 μm, 81 μm, 82 μm, 83 μm, 84 μm, 85 μm, 86 μm, 87 μm, 88 μm, 89 μm, 90 μm, or a range consisting of any two of the above numerical values.
[0167] In the embodiment of the present application, the thickness of the negative electrode film layer is a known meaning in the art, and can be detected by using instruments and methods known in the art. The relevant detection method can refer to the detection standards at home and abroad, the enterprise standards at home and abroad, etc., and those skilled in the art can adaptively change some detection steps / instrument parameters, etc., from the viewpoint of detection accuracy to obtain more accurate detection results. A single detection method can be used for qualitative or quantitative measurement, or multiple detection methods can be combined to measure qualitatively or quantitatively. For example, according to GB / T 17359-2012 "Microbeam Analysis Spectroscopy Quantitative Analysis", a negative electrode plate containing no electrolyte can be used as a sample to perform ion polishing cross-sectional elemental analysis to obtain the thickness of the negative electrode film layer. Furthermore, for example, a negative electrode plate not containing an electrolyte (a negative electrode plate having a negative electrode film layer applied on both sides) is taken, and the thickness of five arbitrary parts of the negative electrode plate is first measured using the thousandth ruler to obtain an average value H1. After the negative electrode film layer is wiped off, the thickness of five arbitrary parts of the remaining current collector is measured to obtain an average value H2. The thickness of the single-layer negative electrode film layer is (H2-H1) / 2.
[0168] In some embodiments, the packed density PD of the negative electrode membrane layer is 1.3 g / cm 3 to 1.7 g / cm 3 When the packing density of the negative electrode film layer is within this range, the negative electrode plate has good dynamic and cycling performance.
[0169] Exemplarily, the compaction density PD of the negative electrode film layer is 1.3 g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 Or, it may be a range consisting of any two of the above values.
[0170] Areal density = weight of negative electrode film layer on one side / area of negative electrode film layer on one side, where both sides of the negative electrode current collector have negative electrode film layers, so the weight of negative electrode film layer on one side = (average weight of electrode plate - average weight of current collector) / 2. Compaction density = areal density / average thickness of negative electrode film layer, where both sides of the negative electrode current collector have negative electrode film layers, so the average thickness of negative electrode film layer = (average thickness of electrode plate - average thickness of current collector) / 2.
[0171] The "average" here may be the average value after five parallel tests.
[0172] In some embodiments, the negative electrode film layer further optionally includes a negative electrode conductive agent. The embodiments of the present application are not particularly limited to the type of the negative electrode conductive agent, and for example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the negative electrode conductive agent is ≦5%.
[0173] In some embodiments, the negative electrode membrane layer further optionally includes a negative electrode adhesive. The embodiments of the present application are not particularly limited to the type of the negative electrode adhesive. For example, the negative electrode adhesive may include at least one of styrene butadiene rubber SBR, water-soluble unsaturated resin SR-1B, water-soluble acrylic acid-based resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS, polyacrylamide PAM, polyvinyl alcohol PVA, sodium alginate SA, and carboxymethyl chitosan CMCS. In some embodiments, based on the total mass of the negative electrode membrane layer, the mass content of the negative electrode adhesive is ≦5%.
[0174] In some embodiments, the negative electrode membrane layer further optionally includes other auxiliary agents. For example, the other auxiliary agents may include thickeners, such as sodium carboxymethylcellulose CMC-Na, PTC thermistor materials, etc. In some embodiments, based on the total mass of the negative electrode membrane layer, the mass content of the other auxiliary agents is ≦2%.
[0175] In some embodiments, the negative electrode current collector may employ a metal foil sheet or a composite current collector. An example of the metal foil sheet may employ copper foil. The composite current collector may include a polymeric base layer and a metal material layer formed on at least one surface of the polymeric base layer. For example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymeric base layer may include at least one of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, and polyethylene.
[0176] In some embodiments, the thickness of the negative electrode current collector is 6 μm or less, and optionally a thin current collector of 4.5 μm to 6 μm.
[0177] The negative electrode current collector of the lithium ion battery of the present application is optionally a thin current collector of 4.5 μm to 6 μm, which can weaken the heat dissipation path of the lithium ion battery and retain some heat in the battery under low SOC discharge state; the combination of the low silicon negative electrode plate with the high content lithium hexafluorophosphate electrolyte system further enhances the beneficial effect on reducing DCR growth at the end of discharge (under low SOC), thereby improving the discharge power at low SOC.
[0178] For example, the thickness of the negative electrode current collector may be 4.0 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm, 4.5 μm, 4.6 μm, 4.7 μm, 4.8 μm, 4.9 μm, 5.0 μm, 5.1 μm, 5.2 μm, 5.3 μm, 5.4 μm, 5.5 μm, 5.6 μm, 5.7 μm, 5.8 μm, 5.9 μm, 6 μm, or a range consisting of any two of the above numerical values.
[0179] In the embodiment of the present application, the thickness of the negative electrode current collector has a meaning known in the art and can be detected using an instrument and a method known in the art. For example, the negative electrode plate is used as a sample, and then the negative electrode film layer on the surface of the negative electrode plate is washed with an organic solvent such as alcohol, and the thickness of the negative electrode current collector is measured with a micrometer.
[0180] The negative electrode film layer is generally obtained by applying a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is generally formed by dispersing a negative electrode active material, an optional conductive agent, an optional adhesive, and other optional auxiliary agents in a solvent and stirring the mixture uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.
[0181] The negative electrode plate does not exclude other additional functional layers other than the negative electrode film layer. For example, in some examples, the negative electrode plate of the embodiment of the present application further includes a conductive undercoating (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode collector and the negative electrode film layer and disposed on the surface of the negative electrode collector. In some other examples, the negative electrode plate of the embodiment of the present application further includes a protective layer covering the surface of the negative electrode film layer.
[0182] [Separator] In some embodiments, the lithium ion battery further comprises a separator, wherein the porosity of the separator is between 30% and 45%.
[0183] Since the amount of lithium hexafluorophosphate added is relatively high, the viscosity of the entire electrolyte is relatively high, and the porosity of the separator is relatively high, which is advantageous for the electrolyte with a relatively high viscosity to permeate the separator, allowing lithium ions to move smoothly.
[0184] Exemplarily, the porosity of the separator may be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, or a range consisting of any two of the above values.
[0185] In the embodiment of the present application, the porosity refers to the percentage of the pore volume in the separator to the total volume of the separator. The porosity can be tested according to the standard GB / T 36363-2018 "Polyolefin Separator for Lithium-Ion Batteries".
[0186] In some embodiments, the separator includes an organic substrate and a coating disposed on at least one side of the organic substrate, the coating including a ceramic layer and / or a polyacrylate layer. The coating may include only a ceramic layer, or only a polyacrylate layer, or a ceramic layer and a polyacrylate layer.
[0187] Alternatively, when the coating comprises a ceramic layer and a polypropylene layer, the polypropylene layer may be provided on at least one surface of the organic substrate and the ceramic layer may be provided on a surface of the polypropylene layer facing away from the organic substrate, or the ceramic layer may be provided on at least one surface of the organic substrate and the polypropylene layer may be provided on a surface of the ceramic layer facing away from the organic substrate.
[0188] The separator has a polyacrylate layer on its outer surface, which gives the outer surface of the separator a certain flexibility, effectively mitigating the volume expansion or contraction of the silicon-based material, and improves the structural stability of the entire electrode assembly.
[0189] The material of the organic substrate is not particularly limited, and any known base film having good chemical stability and mechanical stability can be selected. For example, the organic substrate includes at least one of a porous polyolefin resin film (e.g., at least one of polyethylene, polypropylene, polytetrafluoroethylene, polyvinyl fluoride, and polyvinylidene fluoride), a porous glass fiber, and a porous nonwoven fabric. The organic substrate may be selected from a single layer film or a multilayer composite film. When the organic substrate is a multilayer composite film, the materials of each layer may be the same or different.
[0190] In some embodiments, the thickness of the organic substrate is between 6.6 μm and 7.6 μm.
[0191] When the thickness of the organic base material is within the above range, the transport speed of lithium ions in the negative electrode plate and the transport speed in the separator can be made to be approximately equal, which is advantageous for reducing the risk of worsening concentration polarization and improving discharge performance.
[0192] Exemplarily, the thickness of the organic substrate may be 6.6 μm, 6.7 μm, 6.8 μm, 6.9 μm, 7.0 μm, 7.1 μm, 7.2 μm, 7.3 μm, 7.4 μm, 7.5 μm, 7.6 μm, or a range consisting of any two of the above values.
[0193] In some embodiments, the polyacrylate in the polyacrylate layer may be formed by polymerizing a polymer monomer, the polymer monomer including at least one of a first polymer monomer, a second polymer monomer, and a third polymer monomer. Optionally, the polymer monomer includes a first polymer monomer, a second polymer monomer, and a third polymer monomer. The polyacrylate is formed by polymerizing the above three polymer monomers, which allows the separator to obtain suitable adhesion with the electrode plate, and improves the dynamic performance of the lithium ion battery.
[0194] The first polymer monomer has at least one ester bond and is optionally one or more of methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, vinyl acetate, trifluoroethyl methacrylate, glycidyl methacrylate, or trimethylolpropane triacrylate, and further optionally one or more of methyl methacrylate, lauryl acrylate, lauryl methacrylate, or trimethylolpropane triacrylate.
[0195] The second polymer monomer has at least one cyano bond and is optionally one or more of acrylonitrile, methacrylonitrile, ethacrylonitrile, and further optionally one or more of acrylonitrile, methacrylonitrile.
[0196] The third polymer monomer has at least one amide bond and is optionally one or more of acrylamide, N-methylolacrylamide, N-butoxymethacrylamide, and further optionally one or more of acrylamide, N-methylolacrylamide.
[0197] In some embodiments, the weight ratio of the first polymer monomer, the second polymer monomer, and the third polymer monomer in the formed polyacrylate is (45 to 70):(10 to 25):(10 to 35), for example, (50 to 70):(10 to 25):(10 to 35), (55 to 70):(10 to 25):(10 to 35), (60 to 70):(10 to 25):(10 to 35), (65 to 70):(10 to 25):(10 to 35), (45 to 70):(15 to 25):(10 to 35), (45 to 70):(20 to 25):(10 to 35), (45 to 70):(22 to 25):(10 to 35), (45 to 70):(10 to 25):(15 to 35), (45 to 70):(10 to 25):(20 to 35), (45 to 70):(10 to 25):(25 to 35), (45 to 70):(10 to 25):(30 to 35), (45 to 70):(10 to 25):(32 to 35), and so on.
[0198] In some embodiments, the ceramic layer contains inorganic particles having heat resistance, and the inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having the ability to transport active ions, and inorganic particles in which electrochemical oxidation and reduction can occur.
[0199] In some embodiments, the inorganic particles having a dielectric constant of 5 or more are boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiOx (0 < x ≦ 2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti nO3 (abbreviated as PLZT, 0 < m < 1, 0 < n < 1) and at least one of Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (abbreviated as PMN-PT).
[0200] In some embodiments, the inorganic particles having the ability to transport active ions are lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y -based glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), SiS2-based glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4) and P2S5-based glass (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), at least one of which.
[0201] In some embodiments, the inorganic particles capable of undergoing electrochemical oxidation and reduction include at least one of lithium-containing transition metal oxides, olivine-structured lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium titanium compounds.
[0202] In some embodiments, the ceramic layer may further comprise an adhesive, optionally comprising one or more of polyacrylates, acrylic acid, carboxymethyl cellulose, polyvinylidene fluoride-co-trichloroethylene copolymer, polymethyl methacrylate, polyvinylpyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, tetrafluoroethylene, polyethylene, polypropylene, cyanoethyl pullulan.
[0203] In some embodiments, the coating has a thickness of 1.5 μm to 2.5 μm.
[0204] The thickness of the coating is the thickness of the one-sided coating, specifically including the total thickness of the ceramic layer and the polyacrylate layer, for example, when the coating is provided on both sides of the organic substrate, the thickness of the coating on one side of the organic substrate is the thickness of one side of the coating, or when the coating is provided on one side of the two sides of the organic substrate, the thickness of the coating on this side is the thickness of the one-sided coating. When the thickness of the coating is within the above range, the transport speed of lithium ions in the negative electrode plate and the transport speed in the separator can be almost the same, which reduces the risk of worsening concentration polarization and is favorable for improving discharge performance.
[0205] Illustratively, the coating thickness may be 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, or a range consisting of any two of the foregoing values.
[0206] In some embodiments, the ratio of the thickness of the ceramic layer to the thickness of the polyacrylate layer is (0.5 to 2.0):1, such as 0.5:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, or a range consisting of any two of the foregoing values.
[0207] In the embodiment of the present application, the meaning of the thickness of the organic substrate and coating is the meaning known in the art, and can be detected by using the instruments and methods known in the art, for example, can be tested by using an ion cross section polishing device in combination with a scanning electron microscope. For example, the operation can be performed according to the following steps. First, cut the separator into a test sample of a certain size (for example, 6 mm x 6 mm), sandwich the test sample using two conductive and thermally conductive sheets (for example, copper foil), fix the test sample and the thin piece with adhesive (for example, double-sided adhesive), and press it with a flat iron block of a certain mass (for example, about 400 g) for a certain time (for example, 1 h), so that the gap between the test sample and the copper foil is as small as possible, and then cut it with scissors so that the edges are aligned, and stick it onto a sample stand with conductive adhesive, so that the sample protrudes slightly beyond the sample stand edge. Then, the sample stage is placed in the sample rack, locked and fixed, the argon ion cross-section polisher is turned on to draw a vacuum (e.g., to 10 Pa-4 Pa), the argon gas flow rate (e.g., to 0.15 MPa), voltage (e.g., to 8 KV), and polishing time (e.g., to 2 hours) are set, the sample stage is adjusted to the oscillation mode, and polishing begins. After polishing is completed, an ion-polished cross-section morphology (CP) image of the test sample is obtained using a scanning electron microscope (e.g., ZEISS Sigma 300), and the thickness of the coating and the thickness of the organic substrate are measured.
[0208] In some embodiments, the positive electrode plate, the separator and the negative electrode plate can be manufactured into an electrode assembly by a winding process and / or a stacking process, and it may be understood that the electrode assembly may be a wound electrode assembly or a stacked electrode assembly, and optionally, the electrode assembly is a stacked electrode assembly, which can provide closer contact between the positive electrode plate and the negative electrode plate and further improve the DCR.
[0209] In some embodiments, the lithium ion battery may include an exterior body, which may be used to package the electrode assembly and the electrolyte.
[0210] In some embodiments, the exterior of the lithium ion battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the lithium ion battery may be a pouch, such as a bag-shaped pouch. The material of the pouch may be at least one of plastics, such as polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0211] The embodiment of the present application is not particularly limited to the shape of the lithium ion battery, which may be cylindrical, rectangular, or any other shape. For example, FIG. 1 shows an example of a lithium ion battery 5 with a rectangular structure.
[0212] In some embodiments, as shown in FIG. 2, the exterior body may include a case 51 and a cover plate 53. The case 51 may include a bottom plate and a side plate connected on the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening and seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator may form an electrode assembly 52 by a winding process and / or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is infiltrated into the electrode assembly 52. The number of electrode assemblies 52 included in the lithium ion battery 5 may be one or more, and can be adjusted according to demand.
[0213] The manufacturing method of the lithium ion battery of the embodiment of the present application is known. In some embodiments, a positive electrode plate, a separator, a negative electrode plate, and an electrolyte may be assembled to form a lithium ion battery. For example, the positive electrode plate, the separator, and the negative electrode plate may be formed into an electrode assembly through a winding process and / or a stacking process, and the electrode assembly may be placed in an outer casing, dried, and then injected with an electrolyte, followed by vacuum packaging, standing, chemical formation, shaping, and other processes to obtain a lithium ion battery.
[0214] In some examples of the embodiments of the present application, the lithium ion batteries according to the embodiments of the present application can be assembled into a battery module, and the number of lithium ion batteries included in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0215] Fig. 3 is a schematic diagram of an example battery module 4. As shown in Fig. 3, in the battery module 4, a plurality of lithium ion batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the plurality of lithium ion batteries 5 may be fixed by fasteners.
[0216] Optionally, the battery module 4 may further include a housing having an accommodating space, and the plurality of lithium ion batteries 5 are accommodated in the accommodating space.
[0217] In some embodiments, the above battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0218] 4 and 5 are schematic diagrams of an example battery pack 1. As shown in Fig. 4 and Fig. 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 is used to cover the lower housing 3 and form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0219] power consumption equipment A third aspect of the embodiment of the present application provides a power consuming device, the power consuming device includes at least one of the lithium ion battery, the battery module, or the battery pack of the embodiment of the present application. The lithium ion battery, the battery module, or the battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.
[0220] A power consuming device can choose a lithium ion battery, a battery module or a battery pack according to its usage needs.
[0221] 6 is a schematic diagram of an example power consumer 6, which may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density demands of the power consumer 6, a battery pack or battery module may be employed.
[0222] Another example of a power consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. This power consuming device generally requires a thin design and may employ a lithium ion battery as a power source.
[0223] Working Example The following examples will more specifically describe the contents disclosed in the embodiments of the present application, and these examples are merely for the purpose of discussion and explanation, because it is obvious to those skilled in the art to make various modifications and changes within the scope of the contents disclosed in the embodiments of the present application.Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples can be obtained from commercial sources or synthesized according to conventional methods and can be used directly without further treatment, and all instruments used in the examples can be obtained from commercial sources.
[0224] Example 1 1. Manufacturing of positive electrode plates The positive electrode plate includes a positive electrode current collector and a positive electrode film layer. The positive electrode current collector is an aluminum foil having a thickness of 10 μm. The positive electrode film layer includes a film layer formed by uniformly applying a positive electrode slurry (the solvent is N-methylpyrrolidone (NMP)) to the surface of the aluminum foil of the positive electrode current collector, drying, and cold pressing. The positive electrode film layer includes a positive electrode active material, a conductive agent carbon black, and an adhesive polyvinylidene fluoride (PVDF) in a weight ratio of 97.5:1.4:1.1. The compaction density of the positive electrode film layer is 3.35 g / cm. 3 It was.
[0225] The positive electrode active material has a single crystal structure and has the molecular formula Lid Ni a Co b Mn c M (1-a-b-c) O z wherein the nickel cobalt manganese oxide substrate in the positive electrode active material has the molecular formula LiNi 0.70 Co 0.10 Mn 0.20 Contains compounds that are O2.
[0226] The M elements include 450 ppm of Ti, 1700 ppm of Zr, 1600 ppm of Al, and 120 ppm of (B, S, and P) elements.
[0227] 2. Manufacturing of negative electrode plates The negative electrode plate includes a negative electrode current collector and a negative electrode film layer. The negative electrode current collector is a copper foil having a thickness of 4.5 μm. The negative electrode film layer includes a film layer formed by uniformly applying a negative electrode slurry (the solvent is deionized water) to the surface of the negative electrode current collector copper foil, drying, and cold pressing. The negative electrode film layer includes a negative electrode active material in a weight ratio of 96.2:1.8:1.2:0.8, an adhesive styrene butadiene rubber (SBR), a thickener sodium carboxymethyl cellulose (CMC-Na), and a conductive agent carbon black (Super P).
[0228] The negative electrode active material contained 97% artificial graphite and 3% silicon oxide SiO. The mass content of silicon element relative to the total mass of the negative electrode active material was 1.91%. The compaction density of the negative electrode film layer was 1.4 g / cm. 3 It was.
[0229] 3. Separator The separator can be purchased directly from a separator supplier. The porosity of the separator is 30%, the separator includes an organic substrate (porous polypropylene PP (7 μm)) and a coating, the coating includes a ceramic layer (1 μm) and a polyacrylate layer (1 μm), the ceramic layer is provided on two surfaces of the organic substrate, the ceramic layer includes a membrane layer formed by dissolving an adhesive and inorganic aluminum oxide in N-methylpyrrolidone (NMP) and applying the solution to the organic substrate, the polyacrylate layer is provided on the surface of the ceramic layer away from the organic substrate, and the polyacrylate layer is a membrane layer formed by applying a substance containing polyacrylates to the surface of the ceramic layer.
[0230] 4. Electrolyte production The electrolyte includes an organic solvent, a lithium salt, and an additive, and the organic solvent includes a cyclic carbonate (EC, PC, and BC, the mass ratio of each component is 1:1:1) and a linear carbonate (EMC, DMC, and DEC, the mass ratio of each component is 1:1:1).
[0231] 5. Battery manufacturing The positive electrode plate, separator and negative electrode plate are stacked in order, with the separator located between the positive electrode plate and the negative electrode plate to play the role of isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an outer casing, and after drying, an electrolyte is injected. After vacuum packaging, standing, chemical formation, shaping and other processes, a lithium ion battery is obtained. The liquid retention coefficient of the lithium ion battery is 2.0g / Ah.
[0232] Comparative Example 1 A lithium ion battery was manufactured in a manner similar to that of Example 1, except that the positive electrode active material of Comparative Example 1 was different from that of Example 1, and did not contain the M element.
[0233] Comparative Example 2 and Comparative Example 3 Lithium ion batteries were manufactured in a manner similar to that of Example 1, but the difference from Example 1 is that in Comparative Examples 2 and 3, the components of the electrolyte, particularly the content of lithium hexafluorophosphate, were adjusted.
[0234] Example 2 A lithium ion battery was manufactured in a similar manner to that of Example 1, but differed from Example 1 in that the positive electrode active material in Example 2 was in a different form, and the positive electrode active material in Example 2 used polycrystalline particles.
[0235] Example 3-1 and Example 3-2 A lithium ion battery was manufactured in a manner similar to that of Example 1, but the difference from Example 1 is that the components of the electrolyte, particularly the content of lithium hexafluorophosphate, were adjusted in Examples 3-1 and 3-2.
[0236] Example 4-1 to Example 4-4 A lithium ion battery was manufactured in a manner similar to that of Example 1. The difference from Example 1 is that the positive electrode active materials of Examples 4-1 to 4-4 are different, and the content of at least one of Ti and Zr in the M element of the positive electrode active material is adjusted.
[0237] Examples 4-5 to 4-7 The lithium ion battery was manufactured in a manner similar to that of Example 1, and the difference from Example 1 is that the electrolyte of Examples 4-5 to 4-7 is different, and the content of the first additive in the electrolyte is adjusted.
[0238] Example 5-1 and Example 5-2 A lithium ion battery was manufactured in a manner similar to that of Example 1. The difference from Example 1 is that the positive electrode active materials of Examples 5-1 and 5-2 are different, and the Al content of the M element of the positive electrode active material is adjusted.
[0239] Example 5-3 to Example 5-4 A lithium ion battery was manufactured in a manner similar to that of Example 1. The difference from Example 1 is that the electrolyte of Example 5-3 to Example 5-4 is different, and the content of the second additive in the electrolyte is adjusted.
[0240] Examples 6-1 to 6-3 A lithium ion battery was manufactured in a manner similar to that of Example 1. The difference from Example 1 is that the positive electrode active material and the electrolyte of Example 6-1 to Example 6-3 are different, the positive electrode active material is adjusted to contain the total amount of P, B and S in the M element, and the electrolyte is adjusted to contain the third additive.
[0241] Example 7-1 and Example 7-2 A lithium ion battery was manufactured in a manner similar to that of Example 1, except that the electrolytes in Examples 7-1 and 7-2 were different from those in Example 1, and a fluorinated cyclic carbonate was added to the electrolyte.
[0242] Example 8 A lithium ion battery was manufactured in a manner similar to that of Example 1, and the difference from Example 1 was that the electrolyte of Example 8 was different, and a fourth additive was added to the electrolyte.
[0243] The parameters of the examples and comparative examples are as shown in Tables 1 to 3.
[0244] Performance Testing 1. Lithium-ion cycle performance test At 25°C, the lithium ion batteries prepared in the examples and comparative examples were charged to 4.35V at a rate of 1C and discharged to 2.8V at a rate of 1C for 500 cycles, and the remaining capacity of the lithium ion batteries was recorded as a percentage of the initial capacity.
[0245] Test results The test results are shown in Tables 1 to 3.
[0246] [Table 1]
[0247] In Table 1, the positive electrode active material of Example 1 has a single crystal structure, which has the molecular formula LiNi a Co b Mn c M(1-a-b-c) O2, wherein the nickel cobalt manganese oxide substrate in the positive electrode active material has the molecular formula LiNi 0.70 Co 0.10 Mn 0.20 The compound is O2. The M element includes 450 ppm of Ti element, 1700 ppm of Zr element, 1600 ppm of Al element, and 120 ppm of (B, S and P) elements. The molecular formula of the positive electrode active material of Example 2, Example 3-1 and Example 3-2 is the same as that of Example 1, and Example 2 uses a polycrystalline structure, and Example 3-1 and Example 3-2 use single crystal particles.
[0248] The positive electrode active material of Comparative Example 1 has the molecular formula LiNi 0.70 Co 0.10 Mn 0.20 The compound was O2 and single crystal particles were used.
[0249] As can be seen from Table 1, The content of lithium hexafluorophosphate in Comparative Example 1 is relatively high, but the positive electrode active material in Comparative Example 1 is LiNi 0.70 Co 0.10 Mn 0.20 O2, and its structural stability is relatively low, so that the cycle performance of lithium-ion batteries is still low.
[0250] Comparative Example 2 and Comparative Example 3 both use appropriate positive electrode active material system, the positive electrode active material includes M element, M element includes Ti, Zr, Al, B, S, P, etc., which is favorable to improve the crystal lattice stability of the positive electrode active material system, but Comparative Example 2 uses a relatively low content of lithium hexafluorophosphate (12%), and the relatively low content of lithium hexafluorophosphate produces relatively little lithium fluoride on the surface of the positive electrode active material, which cannot fully protect the positive electrode active material, and there is still a risk that the transition metal ions in the positive electrode active material will dissolve into the electrolyte, which will deteriorate the battery cycle performance. Comparative Example 3 uses a relatively high content of lithium hexafluorophosphate (23%), and the relatively high content of lithium hexafluorophosphate makes the electrolyte system too viscous, which is unfavorable to the movement of lithium ions, which will deteriorate the dynamic performance of the battery.
[0251] The positive electrode active material of Example 1 further comprises M element, the introduction of M element can improve the stability of the positive electrode active material crystal structure, and further combines lithium hexafluorophosphate, the mass content of lithium hexafluorophosphate LiPF6 relative to the total mass of the electrolyte is 15% to 20%, and lithium hexafluorophosphate can form a protective layer with lithium fluoride LiF as the main film component on the surface of the positive electrode active material, thereby mitigating the elution of metal elements and nonmetal elements to a certain extent, and improving the cycle performance of the lithium ion battery. Compared with the positive electrode active material of Example 2 using polycrystalline particles, Example 1 uses single crystal particles, which has a relatively small contact interface between the single crystal particles and the electrolyte, and the risk of side reactions occurring is lower, which is more advantageous in improving cycle performance.
[0252] [Table 2]
[0253] As can be seen from Table 2, The first additive in Examples 4-1 to 4-7 is used in combination with Ti and Zr in the positive electrode active material. Ti and Zr can improve the stability of the positive electrode active material structure, and the first additive can compensate for the power degradation caused by Ti and Zr ions, thereby improving the cycle performance of the lithium ion battery.
[0254] By using the second additive in Examples 5-1 to 5-4 in combination with Al in the positive electrode active material, and in particular by combining lithium difluorophosphate with the Al element in the positive electrode active material, the DCR of the surface of the positive electrode active material can be improved and the interfacial power can be increased.
[0255] [Table 3]
[0256] As can be seen from Table 3, By combining the third additive in Examples 6-1 to 6-3 with at least one element selected from phosphorus (P), sulfur (S) and boron (B) in the positive electrode active material, the DCR of the surface of the positive electrode active material can be improved, and the interfacial power can be increased.
[0257] In Examples 7-1 and 7-2, a fluorinated cyclic carbonate is further added to the electrolyte, and the fluorinated cyclic carbonate can participate in the formation of an SEI film on the surface of the negative electrode active material, and can effectively protect the negative electrode active material, thereby improving the cycle performance of the lithium ion battery.
[0258] In Example 8, a fourth additive is further added to the electrolyte, and the fourth additive can participate in the formation of an SEI film on the surface of the negative electrode active material, which can effectively protect the negative electrode active material, thereby improving the cycle performance of the lithium ion battery.
[0259] Although illustrative embodiments have been shown and described, those skilled in the art should understand that the above-described embodiments should not be construed as limitations on the present application, and that changes, substitutions, and modifications can be made to the embodiments without departing from the spirit, principles, and scope of the present application. [Explanation of symbols]
[0260] 1: battery pack, 2: upper housing, 3: lower housing, 4: battery module, 5: lithium ion battery, 51: case, 52: electrode assembly, 53, cover plate, 6: Power consumption device.
Claims
1. 1. A lithium ion battery, an electrolyte solution comprising a lithium salt, the lithium salt comprising lithium hexafluorophosphate, the mass content of the lithium hexafluorophosphate being 15% to 20% relative to the total mass of the electrolyte solution; A positive electrode plate includes a positive electrode current collector and a positive electrode film layer provided on at least one side of the positive electrode current collector and containing a positive electrode active material, the positive electrode active material having a molecular formula of Li d Ni a Co b Mn c M (1-a-b-c) Q z wherein 0<d≦2.1, 0.6<a<1, 0<b<1, 0<c<1, and 0.6<a+b+c<1, and 1.8≦z≦3.5, the M element includes at least one element selected from the group consisting of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce, and the Q element includes at least one element selected from the group consisting of O and F.
2. The M element includes at least one element selected from the group consisting of Ti and Zr. The electrolyte includes a first additive, and the first additive is lithium difluoro(oxalato)borate LiDFOB and lithium tetrafluoroborate LiBF 4 10. The lithium ion battery of claim 1, comprising at least one of:
3. The lithium ion battery of claim 2 , wherein the M element includes Ti and Zr elements.
4. Based on the total mass of the electrolyte, the mass content of the first additive is 30 ppm to 1200 ppm; Based on the total mass of the positive electrode active material, the mass content of Ti element is 100 ppm to 600 ppm; and / or 4. The lithium ion battery according to claim 2, wherein the mass content of the Zr element is 500 ppm to 2550 ppm based on the total mass of the positive electrode active material.
5. the positive electrode active material comprises a single crystal particle, the single crystal particle comprising an inner region and an outer region, the outer region extending 500 nm from any point on an outer surface of the single crystal particle directly toward an interior of the single crystal particle, The lithium ion battery according to claim 1 , wherein the M element includes at least an Al element distributed in the outer region.
6. 6. The lithium ion battery of claim 5, wherein the electrolyte includes a second additive, the second additive including lithium difluorophosphate.
7. Based on the total mass of the positive electrode active material, the mass content of Al element is 500 ppm to 3000 ppm; 7. The lithium ion battery according to claim 6, wherein the mass content of the second additive is 100 ppm to 3000 ppm based on the total mass of the electrolyte.
8. The M element further includes at least one element selected from the group consisting of P, S, and B, wherein at least one of the P, S, and B elements is distributed in the outer region; 8. The lithium ion battery of claim 5, wherein the electrolyte solution includes a third additive, and the third additive includes lithium fluorosulfonate.
9. Based on the total mass of the positive electrode active material, the total mass content of P, S and B elements is 10 ppm to 800 ppm; 9. The lithium ion battery according to claim 8, wherein the mass content of the third additive is 50 ppm to 200 ppm based on the total mass of the electrolyte.
10. The lithium ion battery according to any one of claims 1 to 9, wherein the electrolyte solution contains a cyclic carbonate, and the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate, based on the total mass of the electrolyte solution, is (0.60 to 2.50):
1.
11. 11. The lithium ion battery according to claim 10, wherein the ratio of the mass content of the cyclic carbonate to the mass content of the lithium hexafluorophosphate is (1.00 to 1.65):1, based on the total mass of the electrolyte solution.
12. Based on the total mass of the electrolyte, the mass content of the cyclic carbonate is 20% to 30%; and / or 12. The lithium ion battery according to claim 10 or 11, wherein the cyclic carbonate includes at least one of ethylene carbonate EC, propylene carbonate PC, and butylene carbonate BC.
13. 13. The lithium ion battery according to claim 1, further comprising a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode film layer provided on at least one side of the negative electrode current collector and containing a negative electrode active material, the negative electrode active material containing a carbon element and a silicon element, and a ratio of a mass content of the silicon element to a mass content of the carbon element based on a total mass of the negative electrode active material is from (0.3:99.7) to (3:97).
14. 14. The lithium ion battery according to claim 13, wherein the electrolyte solution contains a fluorinated cyclic carbonate, and the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the silicon element relative to the total mass of the electrolyte solution is (0.5 to 9.5):
1.
15. 15. The lithium ion battery according to claim 14, wherein the ratio of the mass content of the fluorinated cyclic carbonate to the mass content of the silicon element relative to the total mass of the electrolyte is (1 to 2):
1.
16. The mass content of the fluorinated cyclic carbonate is from 0.95% to 5.8%, based on the total mass of the electrolyte; and / or 16. The lithium ion battery of claim 14 or 15, wherein the fluorinated cyclic carbonate comprises at least one of monofluoroethylene carbonate (FEC), bisfluoroethylene carbonate (DFEC), and trifluoropropylene carbonate (TFPC).
17. the mass content of the fluorinated cyclic carbonate is 1.5% to 3%, based on the total mass of the electrolyte; and / or 17. The lithium ion battery of claim 16, wherein the fluorinated cyclic carbonate comprises monofluoroethylene carbonate FEC.
18. 18. The lithium ion battery according to claim 13, wherein the ratio of the compaction density of the positive electrode film layer to the compaction density of the negative electrode film layer is (2 to 2.5):
1.
19. The electrolyte further includes a fourth additive, which is composed of 1,3-propane sultone PS, vinylene carbonate VC, and lithium fluorosulfonate LiSO 3 19. The lithium ion battery of claim 1 , further comprising at least one of: F.
20. Based on the total mass of the electrolyte, the mass content of the 1,3-propane sultone PS is 0.1% to 1%; and / or 20. The lithium ion battery of claim 19, wherein the mass content of the vinylene carbonate VC is 0.1% to 1% based on the total mass of the electrolyte.
21. A battery comprising the lithium ion battery of any one of claims 1 to 20.
22. 22. A power consuming device comprising the battery of claim 21.
Citation Information
Patent Citations
Lithium ion secondary battery
JP2000149945A
Positive electrode active material, manufacturing method thereof, secondary battery, battery module, battery pack and device
JP2023513558A
Non-aqueous electrolyte for lithium secondary battery, and lithium secondary battery comprising same
WO2023027547A1
Lithium ion battery, battery, and electrical device
WO2024153269A2
Cited By
Lithium-ion battery, battery, and electric apparatus
US12548802B2
Lithium-ion battery, battery, and electric apparatus
US20250140895A1
Positive electrode active material for lithium ion secondary battery, positive electrode for lithium ion secondary battery, and lithium ion secondary battery
WO2026205578A1